GENDER, POLITIK DAN AGAMA - Dendi Sutarto (JURNAL TRIAS POLITIKA, 2017)
Muhammadiyah is the largest religious social movement in Indonesia, based in Yogyakarta, Yogyakarta. The organization was founded on 8 Dhu al-Hijjah 1330 H or November 18, 1912 in Yogyakarta by KHAhmad Dahlan, the movement known as the Islamic purification movement " amal ma’ruf nahi munkar ", but what counts Muhammadiyah became the basis of religion in the construction and reproduction root doctrine on value socio-cultural-value in the relationship between men and women as well as a political legitimacy on gender inequality in Muhammadiyah. This research is a field research, using methods kualitatfi with the sociological approach-fenomenolis reinforced by some theoretical analysis of Antonio Gramsci with terminology hegemony, Michel Foucult, with power relations the history of sexuality and assisted by other theories one structural functionalism. From the findings of this study that gender inequality and the strong role of religion as a value in the process of construction and reproduction of gender in the Muhammadiyah movement.  Keywords: religion, gender, politics, construction, muhammadiyahMuhammadiyah merupakan gerakan sosial keagamaan yang terbesar di Indonesia, yang berpusat di Yogyakarta, Daerah Istimewa Yogyakarta. Organisasi ini didirikan pada 8 Dzulhijjah 1330 H atau 18 Nopember 1912 M di Yogyakarta oleh K.H.Ahmad Dahlan, gerakan ini dikenal sebagai gerakan purifikasi Islam “amal ma’ruf nahi munkar”, namun problemnya basis agama di Muhammadiyah menjadi akar kontruksi dan reproduksi doktrin atas nilai-nilai sosio cultural dalam relasi laki-laki dan perempuan sekaligus menjadi legitimasi politik atas ketidakadilan gender di Muhammadiyah. Penelitian ini adalah penelitian lapangan, menggunakan metode kualitatfi dengan pendekatan sosiologis-fenomenolis yang diperkuat oleh beberapa analisis teoritis dari Antonio Gramsci dengan terminology hegomoni, Michel Foucult, dengan relasi kuasa the history of sexuality dan dibantu oleh teori lainnya salah satunya fungsionalisme struktural. Dari hasil temuan penelitian ini bahwa ketimpangan gender dan kuatnya peran agama sebagai nilai dalam proses konstruksi dan reproduksi gender di gerakan Muhammadiyah. Kata kunci: agama, gender, politik, konstruksi, muhammadiyah